Wt1 and retinoic acid signaling in the subcoelomic mesenchyme control the development of the pleuropericardial membranes and the sinus horns. - Norden, J; Grieskamp, T; Lausch, E; van Wijk, B; van den Hoff, M; Englert, C; Petry, M; Mommersteeg, M; Christoffels, V; Niederreither, K; Kispert, A (2010)
RATIONALE: The cardiac venous pole is a common focus of congenital malformations and atrial arrhythmias, yet little is known about the cellular and molecular mechanisms that regulate its development. The systemic venous return myocardium (sinus node and sinus horns) forms only late in cardiogenesis from a pool of pericardial mesenchymal precursor cells. OBJECTIVE: To analyze the cellular and molecular mechanisms directing the formation of the fetal sinus horns. METHODS AND RESULTS: We analyzed embryos deficient for the Wt1 (Wilms tumor 1) gene and observed a failure to form myocardialized sinus horns. Instead, the cardinal veins become embedded laterally in the pleuropericardial membranes that remain tethered to the lateral body wall by the persisting subcoelomic mesenchyme, a finding that correlates with decreased apoptosis in this region. We show by expression analysis and lineage tracing studies that Wt1 is expressed in the subcoelomic mesenchyme surrounding the cardinal veins, but that this Wt1-positive mesenchyme does not contribute cells to the sinus horn myocardium. Expression of the Raldh2 (aldehyde dehydrogenase family 1, subfamily A2) gene was lost from this mesenchyme in Wt1(-/-) embryos. Phenotypic analysis of Raldh2 mutant mice rescued from early cardiac defects by retinoic acid food supply revealed defects of the venous pole and pericardium highly similar to those of Wt1(-/-) mice. CONCLUSIONS: Pericardium and sinus horn formation are coupled and depend on the expansion and correct temporal release of pleuropericardial membranes from the underlying subcoelomic mesenchyme. Wt1 and downstream Raldh2/retinoic acid signaling are crucial regulators of this process. Thus, our results provide novel insight into the genetic and cellular pathways regulating the posterior extension of the mammalian heart and the formation of its coelomic lining.